2006
DOI: 10.1007/s10517-006-0462-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and immunohistochemical study of hepatic stellate cells over the course of infectious viral fibrosis and cirrhosis of the liver

Abstract: The dynamics of structural and functional changes in stellate cells in liver biopsy specimens (from lipid-containing to fibrogenous phenotype) was studied during the development of infectious viral fibrosis and cirrhosis of the liver using ultrastructural, immunohistochemical, and morphometric methods. The priority role of stellate cells in the synthesis of extracellular matrix components is emphasized. Resorption of perihepatocellular collagen fibrils is associated with parenchymatous liver cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…HSCs treated with PSCs did not contain lipid droplets compared to HSC controls. The number of lipid-containing HSCs decreased signi cantly during the transformation phase of liver cirrhosis, indicating that the cells underwent brogenic transformation [18]. All features resulting from treatment of HSCs with PSCs, including multiplication or disappearance of the nucleus, enlargement of the Golgi apparatus, changes in the cytoplasm, and nally, transformation of cytoplasm into autophagosomes, indicate brogenic transformation compared to the HSC controls.…”
Section: Discussionmentioning
confidence: 99%
“…HSCs treated with PSCs did not contain lipid droplets compared to HSC controls. The number of lipid-containing HSCs decreased signi cantly during the transformation phase of liver cirrhosis, indicating that the cells underwent brogenic transformation [18]. All features resulting from treatment of HSCs with PSCs, including multiplication or disappearance of the nucleus, enlargement of the Golgi apparatus, changes in the cytoplasm, and nally, transformation of cytoplasm into autophagosomes, indicate brogenic transformation compared to the HSC controls.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, HSCs exposed to PSCs did not contain lipid droplets, whereas the HSC controls did. The number of lipid-containing HSCs decreased significantly during the transformative phases of liver fibrosis, which indicated that they underwent fibrogenic transformation [ 24 ]. All of the features resulting from the exposure of the HSCs to the PSCs, including the division or malformation and irregularity of the nucleus, and the microvilli on the cell membrane increasing and the mitochondria swelling are indicative of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Fasciola hepatica and Dicrocoelium dendriticum . HSCs play an important role in the development of fibrosis and other stages of cirrhosis [ 24 , 30 ]. TGF-β plays a role in the differentiation of HSCs; it is the main factor that activates these cells, which leads to collagen deposition [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of morphological features of HSCs in fibrotic livers were studied by electron microscopy [ 115 , 116 ]. In both studies, liver biopsies of human patients with chronic hepatitis C were imaged.…”
Section: Hepatic Stellate Cells In Healthy and Diseased Livermentioning
confidence: 99%
“…In livers with increasing fibrosis severity scores, numbers of LD-containing HSCs decreased [ 116 ]. Even in the most pronounced fibrotic stages, LDs did not disappear completely [ 115 ]. In addition, a comparison of HSCs isolated by two different FACS (Fluorescent Activated Cell Sorting) protocols underlined the relation between LD size and activation status: retinoid autofluorescence-sorted cells—associated with a quiescent state—display larger LDs than cells sorted by GFP under a collagen promotor—typically linked to a more activated state [ 100 ].…”
Section: Hepatic Stellate Cells In Healthy and Diseased Livermentioning
confidence: 99%